2021
DOI: 10.1007/s00540-021-02992-y
|View full text |Cite
|
Sign up to set email alerts
|

The short-term effect of COVID-19 pandemic on disability, pain intensity, psychological status, and exercise habits in patients with chronic pain

Abstract: Purpose The coronavirus disease 2019 (COVID-19) pandemic has affected the lives of people worldwide. The first declaration of a state of emergency in Japan, based on the Act on Special Measures for the Prevention and Control of the Novel Coronavirus, was issued from 16 April 2020 to 14 May 2020 to reduce person-to-person contact. Restrictions on going out, participating in community activities, and visiting hospitals were in place. This study investigates the short-term effects of the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Therefore, we appreciate the existence of other investigations about the effects of the current pandemic on patients with chronic pain that examined larger cohorts and seemingly produced results sometimes contradictory to ours (i.e., no relevant effect of the pandemic on the patients). [ 26 , 27 ] For several reasons though, these results cannot be compared to ours. While retrospective data analysis/no use of validated questionnaires/sole assessment of pain intensity are some reasons to name, perhaps the most pivotal point to consider is the fact that they did not differentiate across pain etiologies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, we appreciate the existence of other investigations about the effects of the current pandemic on patients with chronic pain that examined larger cohorts and seemingly produced results sometimes contradictory to ours (i.e., no relevant effect of the pandemic on the patients). [ 26 , 27 ] For several reasons though, these results cannot be compared to ours. While retrospective data analysis/no use of validated questionnaires/sole assessment of pain intensity are some reasons to name, perhaps the most pivotal point to consider is the fact that they did not differentiate across pain etiologies.…”
Section: Discussionmentioning
confidence: 64%
“…Due to the long-term observation of our cohort throughout the entire year, we have now been able to show that the perception of pain intensity was indeed dependent on pandemic activity, with lower pain intensity during lockdown and higher during loosened regulations, whereas domains like sleep, mood and quality of life did not change significantly in the validated measures, which is consistent with previous reports. [ 26 , 27 ] In our cohort, the consideration of the co-factor “health care” was decisive: patients who reported medical disadvantages had a lower quality of life upon EQ-5D and were significantly more worried about their health.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have documented increased psychological distress during previous epidemics or pandemics, including Ebola virus disease in 2014 [ 35 , 36 ] and severe acute respiratory syndrome (SARS) in 2003 [37] . Psychological distress during the COVID-19 pandemic has been shown to negatively affect health, leading to greater pain severity in patients with chronic pain [ 38 , 39 ] and reduction in patients with musculoskeletal conditions [40] . Our study suggests that individuals with psychological distress, especially depression, experience more detrimental impact on their pain and their satisfaction with participation in social roles compared with those without psychological distress as a response to the external stress of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Together these findings consistently indicate that the social distancing measures had a negative impact on the physical, psychological, and social function of individuals with chronic pain. Moreover, research has consistently identified a group of variables that are associated with the negative impact of social distancing measures on patients with chronic pain and their poor adjustment to them (e.g., catastrophic thinking, anxiety; [ 5 , 7 ]).…”
Section: Introductionmentioning
confidence: 99%